1998
DOI: 10.1177/0734242x9801600106
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia and nitrogen fluxes in landfill sites: applicability to sustainable landfilling

Abstract: European legislation imposes tough restrictions on the quality of landfill leachate discharges, of which a major component is ammonia. Thus, there is a pressing need, particularly for oper ators who will have to meet these discharge standards, for a greater understanding of the origin and transformations of ammonia and other nitrogenous compounds from landfills. Moreover, with the concept of 'sustainability' being applied to landfilling, the industry will need to meet the challenge of accelerating the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(52 citation statements)
references
References 53 publications
2
45
0
2
Order By: Relevance
“…Nevertheless, in some cases we observed nitrate reduction without gaseous nitrogen production. This phenomenon has been observed at least once before in landfill 5 and also in marine sediment. 6 Using a stepwise multiple regression model, H 2 S concentration was the unique parameter found to have a negative effect on N 2 production.…”
supporting
confidence: 62%
“…Nevertheless, in some cases we observed nitrate reduction without gaseous nitrogen production. This phenomenon has been observed at least once before in landfill 5 and also in marine sediment. 6 Using a stepwise multiple regression model, H 2 S concentration was the unique parameter found to have a negative effect on N 2 production.…”
supporting
confidence: 62%
“…Le pH acide obtenu lors de la phase acidogène donne un caractère agressif aux lixiviats et favorise ainsi la dissolution des composés minéraux (KJELDSEN et al, 2002). Contrairement à la matière organique, la concentration en azote ammoniacal ne baisse pas de manière significative au cours du temps (BURTON et WATSON-CRAIK, 1998). Même dans les lixiviats « matures », on retrouve des concentrations élevées en azote ammoniacal (AMOKRANE et al, 1997;SINGH et al, 2012).…”
Section: Caractéristiques Des Lixiviats De Sites D'enfouissementunclassified
“…Même dans les lixiviats « matures », on retrouve des concentrations élevées en azote ammoniacal (AMOKRANE et al, 1997;SINGH et al, 2012). Cela est dû en partie à l'ammonification de substances azotées comme les protéines et les acides aminés (BURTON et WATSON-CRAIK, 1998) et le milieu anaérobie de la décharge qui ne favorise pas les réactions de nitrification. De ce fait, la pollution azotée est considérée comme un polluant à long terme dans les décharges (KJELDSEN et al, 2002).…”
Section: Caractéristiques Des Lixiviats De Sites D'enfouissementunclassified
“…Ammonia typically accumulates in leachate because there is no mechanism for its biodegradation under methanogenic conditions. Some have suggested that ammonia is the most significant long-term pollution problem at landfills (11,15,17,18). Calculations of potential ammonia volatilization from landfills indicate that this mechanism can account for less than a 10% loss.…”
Section: Characteristics Of Leachate From Well-decomposed Refusementioning
confidence: 99%